Pengaruh Pembinaan Disiplin dan Motivasi Kerja terhadap Kepuasan Kerja bagian Checker PT. XYZ pada Region Jawa Bagian Barat - Alfitto Deannova, Ahmad Taufik; Dian Lestari (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of discipline and work motivation development on job satisfaction in the checker department at PT. XYZ in the West Java region. The research method used was a quantitative approach with descriptive and associative research. Data collection techniques were conducted through questionnaires, interviews, and documentation, while data analysis used multiple linear regression with the help of SPSS 26.0. The results showed that discipline and work motivation development had a positive and significant effect on job satisfaction, both partially and simultaneously. The coefficient of determination (R²) of 0.851 indicates that 85.1% of the variation in job satisfaction is explained by discipline and work motivation development, while the remaining 14.9% is influenced by other factors outside the study. The conclusion of this study is that improving discipline and work motivation development is crucial in improving employee job satisfaction at PT. XYZ.   Keywords: Discipline Development, Work Motivation, Job Satisfaction, Checker